Editores Gráficos para Estruturas com Composições - Muchaluat, Débora Christina; Soares, Luiz Fernando Gomes; Casanova, Marco Antonio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1996)
This paper discusses compound graphs graphical editors. Besides offering relations modeled by arcs, also offer composition relations modeled by the content of nested subgraphs. When dealing with large and complex structures, we must not show all its components simultaneously, because the diagram would become very confusing and illegible. Our proposal presents an algorithm for filtering information using an extension of the fisheye-view strategy for compound graphs. This technique could be applied to many fields where the using of graphical editors is crucial. We present an implementation of our proposal for hypermedia systems, by building browsers that use and validate the algorithm.